Electronic sales made by micro and small enterprises to federal government: a critical analysis of the data on the breadth of processes - Carvalho, Luis Augusto de; Ribeiro, Rosinei Batista [UNESP]; Campos, Rose Lima de Moraes [UNESP]; Sabbadini, Francisco Santos; Silva, Caio Fernando da; Luciano, Erik Leonel (Sindicato Secretarias Estado Sao Paulo, 2023)
The creation of e-government, changes have occurred both in the products offered to citizens and in the work process. Among these changes were the purchases of goods and services, which began to be made via reverse auctions on the Internet, through electronic purchasing portals. The ease of the purchasing process, the low cost of participation, and the laws created have given Micro and Small Enterprises the opportunity to sell electronically to the Public Administration. Studies carried out by SEBRAE (Brazilian Service of Support to Micro and Small Enterprises) point to the growing trend of this activity as a differential, ensuring the continuity of the companies' activities. The present work aimed to present an analysis of electronic sales, by Micro and Small Enterprises, to the Federal Government, in the period from January to December 2013. To this end, it is performed quantitative exploratory research, using, as techniques for data collection, bibliographic and documentary research. The data were obtained through the Federal Government's purchasing statistics, disclosed on its purchasing portal. Thus, it was possible to know the participation of Micro and Small Enterprises in the electronic purchases of the Federal Government in the period from January to December 2013. The results show that 30% of the Federal Government's electronic purchases, representing R$ 14.1 billion, in the period from January to December 2013, were acquired from Micro and Small Enterprises, compared to the same period in 2012, showing an increase of 60% in the volume of sales by Micro and Small Enterprises.
Keywords: Electronic Commerce; Public Administration; Electronic Sales; Small Business Enterprise